2009
DOI: 10.1186/1471-230x-9-25
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing incidence of peptic ulcer complications after the introduction of the proton pump inhibitors, a study of the Swedish population from 1974–2002

Abstract: BackgroundDespite a decreasing incidence of peptic ulcer disease, most previous studies report a stabile incidence of ulcer complications. We wanted to investigate the incidence of peptic ulcer complications in Sweden before and after the introduction of the proton pump inhibitors (PPI) in 1988 and compare these data to the sales of non-steroid anti-inflammatory drugs (NSAID) and acetylsalicylic acid (ASA).MethodsAll cases of gastric and duodenal ulcer complications diagnosed in Sweden from 1974 to 2002 were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 46 publications
(55 reference statements)
7
53
1
1
Order By: Relevance
“…Although the safety and efficacy of the laparoscopic approach has been sufficiently proven, its incorporation into daily practice remains low. This might be due to the fact that surgery for perforated gastroduodenal ulcers is still declining due to increasing use of H 2 -receptor antagonists and proton pump inhibitors as well as H. pylori eradication [30,31,32]. Therefore, we postulate that the low rate of laparoscopy in our series might be due to decreasing experience with this type of surgery overall.…”
Section: Discussioncontrasting
confidence: 42%
“…Although the safety and efficacy of the laparoscopic approach has been sufficiently proven, its incorporation into daily practice remains low. This might be due to the fact that surgery for perforated gastroduodenal ulcers is still declining due to increasing use of H 2 -receptor antagonists and proton pump inhibitors as well as H. pylori eradication [30,31,32]. Therefore, we postulate that the low rate of laparoscopy in our series might be due to decreasing experience with this type of surgery overall.…”
Section: Discussioncontrasting
confidence: 42%
“…The reasons for these discrepancies are unclear, as a decrease of Helicobacter pylori (H. pylori) infection among the population, increasing H. pylori eradication therapy and increasing PPI use across Europe should be accompanied by a progressive decrease in peptic ulcer complications. 14,15,17 The variability in the use of low-dose aspirin (ASA) and gastro-protective Mean comparison among categories: P-value < 0.001.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Our data also show very low rates of mortality due to peptic ulcer bleeding, which is consistent with other studies. 8,14,15 The lack of improvement in case fatality rates is usually linked to a progressively ageing population with increasing numbers of co-morbidities, despite data that show better bleeding management strategies associated with reduction in the risk of rebleeding and a reduced need for surgery. 20 In any case, our data agree with a recent USA report 8 that shows an overall decrease (absolute numbers) in in-hospital deaths linked to GI bleeding diagnoses between 1998 and 2006, because of a decrease in the number of hospitalisations.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that the sales of NSAIDs in Sweden increased during the period 1978-2002. 11 The present study shows that sales have decreased since 2004 with regard to both genders, and this decrease is more obvious in women and in the population aged over 75 (data not shown). This decline might contribute to the decreasing trend of peptic ulcer death and re-bleeding in women.…”
Section: This Study Indicates That Sales Of Nsaids and Ppis (Inverselmentioning
confidence: 44%